Education-to-job mismatch and the risk of work injury. Issue 2 (9th July 2012) - Premji, Stephanie; Smith, Peter M
Abstract : Objectives: To examine the association between education-to-job mismatch and work injury. Methods: Cross-sectional data from the 2003 and 2005 Canadian Community Health Surveys (n=63 462) were used to examine the relationship between having an educational level that is incongruent with occupational skills requirements and the risk of sustaining a work injury requiring medical attention or a work-related repetitive movement injury (RMI). The effect on injury of the interaction of overeducation with recent immigrant status was also examined. Models were stratified by sex and adjusted for possible confounders. Occupational physical demands were conceptualised as a potential mediating variable. Results: After adjustment for covariates, over-education was associated with work injury and RMI for both sexes. Adjustment for occupational demands attenuated the impact on work injury but did not eliminate the effect on RMI among men. The interaction of over-education and recent immigrant status resulted among men in a fourfold increase in the odds of work injury compared with non-recent immigrants who were not over-educated. After adjustment for occupational demands, over-educated recent immigrant men still had more than a twofold increase in the odds of injury. Conclusions: The risk of sustaining a work injury is higher among those whose education exceeds that of job requirements. These findings highlight the need to address barriers to suitable employment, particularly among recent immigrants.